Powder coating composition
Patent Information
- Application Number
- CN202280016121.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-02-22
- Filing Date
- 2022-02-22
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-02-22
AI Technical Summary
尽管厚涂布能够通过旋转涂衬(Rotolining)法来进行,但是使用目标限于能够应用旋转涂时的具有罐或管的圆形横截面的结构的内表面(非专利文献1)
[0022]本发明提供了一种含有填料的热熔性氟树脂粉末涂料组合物,该组合物的一次可涂布的膜厚度较大,外覆层的膜厚度极限较大,并且可进行厚涂布。
Smart Images

Figure BDA0004404601400000131 
Figure BDA0004404601400000132 
Figure BDA0004404601400000141
Abstract
Description
[0001] Cross-reference to related applications
[0002] This application claims priority to Japanese Application No. 2021-26033, filed on February 22, 2021, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0003] This invention relates to a hot-melt fluoropolymer powder coating composition containing fillers, which can be thickly coated on a vertical surface by electrostatic powder coating. Background Technology
[0004] In addition to their extremely low coefficient of friction and non-stickiness, fluoropolymers possess excellent heat resistance, chemical resistance, electrical properties, and mechanical properties, leading to their widespread use in all types of industrial applications, such as chemical, mechanical, and electrical installations. In particular, hot-melt fluoropolymers exhibit fluidity at temperatures above their melting point, and therefore, when formed in coatings, they suppress pinhole formation, thus allowing their use in coating compositions for fluoropolymer coatings.
[0005] Patent document 1 discloses aqueous liquid coatings based on fluoropolymers. These aqueous liquid coatings, used as so-called slurry coatings, have high concentrations and viscosities, thus allowing for a thick coating layer. However, unlike powder coatings, slurry coatings are prone to foaming when the solvent (dispersion medium) evaporates. To prevent this, various solvents are used and multi-stage baking and drying processes are required, leading to environmental problems such as solvent evaporation, longer drying times for slurries, greater difficulty in storing and managing slurries compared to powder coatings, and difficulty in coating materials with complex shapes with slurries.
[0006] On the other hand, hot-melt fluoropolymer powder coatings have the following advantages: they can be applied in thick coats without using volatile liquid media, the coatings can be reused, and they do not generate VOCs (volatile organic compounds). Electrostatic coating is commonly used as a powder coating method for hot-melt fluoropolymer powder coatings, in which the material to be coated and the powder coating are charged and then coated. Furthermore, when using fillers to impart various properties (such as conductivity, abrasion resistance, wear resistance, etc.) or to adjust the appearance (such as color, brightness, etc.) of hot-melt fluoropolymer powder coatings, the particles of the hot-melt fluoropolymer powder coating can be mixed with the fillers. However, from the perspectives of thick coatability, coating durability, prevention of filler detachment from the coating, and prevention of coating changes, the filler particles are preferably dispersed in the hot-melt fluoropolymer powder particles (e.g., Patent Documents 2 and 3).
[0007] On the other hand, in recent years, there has been a growing demand for coatings that offer superior durability and corrosion resistance, and the ability to apply thick coatings is required to improve productivity and reduce processing costs. Furthermore, to increase productivity, a larger film thickness achievable in a single coating application is preferred to reduce the number of outer coating layers. However, compared to filler-free coatings, hot-melt fluoropolymer powder coatings containing fillers (especially conductive fillers) exhibit poorer thick-coating properties. This is believed to be because even if the filler is internally dispersed as described above, the presence of conductive fillers makes it difficult to apply a charge to the powder particles during electrostatic coating, thus leading to particle desorption. On the other hand, conductive coatings are used to prevent charging, but thick coatings are also required to provide corrosion resistance. Moreover, to date, conductive coatings have typically only provided conductivity to the surface layer, but conductivity is needed throughout the entire thick coating film.
[0008] Furthermore, it is known that hot-melt fluoropolymer powder coatings such as PFA can be applied in thicker layers compared to liquid coatings. Although thick coatings can be achieved by spin-lining, their application is limited to the inner surfaces of structures with a circular cross-section, such as cans or tubes, where spin-lining can be applied (Non-Patent Document 1).
[0009] Existing technical documents
[0010] Patent Document 1: Japanese Patent Publication 3321805
[0011] Patent Document 2: Japanese published examined application H5-73147
[0012] Patent Document 3: Japanese published examined application S52-44576
[0013] Non-patent literature
[0014] Non-patent literature 1: Corrosion-Resistant Lining and Coating Guidebook (published by the Japan Fluoropolymers Industry Association), page 9, Table 1 Summary of the Invention
[0015] The problem to be solved by the present invention
[0016] The purpose of this invention is to provide a hot-melt fluororesin powder coating composition containing fillers, which has a high film thickness that can be coated in one step and a high film thickness limit for the outer coating, and can be used for thick coating.
[0017] Problem Solving Methods
[0018] The present invention is a powder coating composition, which is a powder mixture containing: first hot-melt fluoropolymer particles having an average particle size of 2 μm to 100 μm, wherein filler is dispersed in the particles; second hot-melt fluoropolymer particles having an average particle size of 10 μm to 200 μm; and charge control agent particles.
[0019] In the powder coating composition of the present invention, the ratio of the first hot-melt fluoropolymer particles to the second hot-melt fluoropolymer particles is preferably 1 to 60% by weight: 40 to 99% by weight, and the amount of charge control agent particles is 0.01% to 5% by weight of the total amount of the powder coating composition. The average particle size of the second hot-melt fluoropolymer particles is preferably larger than the average particle size of the first hot-melt fluoropolymer particles. Furthermore, the filler is preferably a conductive filler, and more preferably a carbon material having a graphene structure. Furthermore, the charge control agent particles are preferably graphite. Furthermore, the hot-melt fluoropolymer is preferably a perfluorinated resin.
[0020] Another aspect of the invention is a coating film prepared from a powder coating composition, wherein the film thickness is preferably 100 μm or greater.
[0021] Effects of the present invention
[0022] The present invention provides a hot-melt fluororesin powder coating composition containing fillers, which has a large film thickness that can be coated in one step, a large limit on the film thickness of the outer coating, and can be used for thick coating. Detailed Implementation
[0023] The powder coating composition of the present invention is a powder coating composition containing the following substances as a powder mixture: (1) a first hot-melt fluoropolymer particles, (2) a second hot-melt fluoropolymer particles, and (3) charge control agent particles.
[0024] (1) First hot-melt fluororesin particles
[0025] The first hot-melt fluororesin particles of the present invention are described below. The first hot-melt fluororesin particles of the present invention are particles with an average particle size of 2 μm to 100 μm, wherein filler is dispersed in the hot-melt fluororesin, and are manufactured from the hot-melt fluororesin and filler.
[0026] The hot-melt fluoropolymers used in this invention can be suitably selected from resins referred to as hot-melt fluoropolymers. Examples include polymers or copolymers of monomers selected from tetrafluoroethylene, trifluoroethylene, hexafluoropropylene, perfluoro(alkyl vinyl ether), vinylidene fluoride, and vinyl fluoride, copolymers of these monomers with ethylene, propylene, butene, pentene, hexene, or another monomer having a double bond, or acetylene, propyne, or another monomer having a triple bond, etc. Specific examples of hot-melt fluoropolymers include low molecular weight hot-melt polytetrafluoroethylene (hot-melt PTFE), tetrafluoroethylene perfluoro(alkyl vinyl ether) copolymer (PFA), tetrafluoroethylene hexafluoropropylene copolymer (FEP), tetrafluoroethylene hexafluoropropylene perfluoro(alkyl vinyl ether) copolymer, tetrafluoroethylene copolymer, polyvinylidene fluoride, polychlorotrifluoroethylene, trifluoroethylene copolymer, etc.
[0027] Among these hot-melt fluoropolymers, perfluoropolymers, such as hot-melt PTFE, PFA and FEP, tetrafluoroethylene, hexafluoropropylene, and perfluoro(alkyl vinyl ether) copolymers, are particularly preferred from the perspective of non-stickiness and heat resistance of the coating. Of these, PFA is preferred from the perspective of heat resistance. When using PFA, the alkyl groups of the perfluoro(alkyl vinyl ether) in PFA preferably have 1 to 5 carbon atoms, and more preferably 1 to 3 carbon atoms. Furthermore, the amount of perfluoro(alkyl vinyl ether) in PFA is preferably in the range of 1% to 50% by weight.
[0028] Furthermore, considering good formability during high-temperature melting, the hot-melt fluoropolymer used in this invention is preferably a hot-melt fluoropolymer with flowability at temperatures above its melting point. Specifically, the melt flow rate (MFR) of the hot-melt fluoropolymer is preferably 0.1 g / 10 min or more, and more preferably 0.5 g / 10 min or more. Examples of resins include PFA, FEP, and tetrafluoroethylene, hexafluoropropylene, and perfluoro(alkyl vinyl ether) copolymers. PFA, with its high melting point and excellent thermal flowability, is particularly preferred. On the other hand, if the MFR is too high (melt viscosity too low), appearance defects (dents) due to sagging or shrinkage may easily occur during repeated coating and baking, and the formation of a thick film becomes difficult, which is not preferred. Specifically, the MFR of the hot-melt fluoropolymer is preferably 15 g / 10 min or less, more preferably 10 g / 10 min or less, and particularly preferably 5 g / 10 min or less.
[0029] The hot-melt fluoropolymer used in this invention can be blended with two or more hot-melt fluoropolymers according to the desired properties. Additionally, it may also contain non-hot-melt polytetrafluoroethylene.
[0030] In the first hot-melt fluororesin particles of the present invention, the filler is dispersed inside the particles. Here, the filler material is preferably uniformly dispersed inside the particles. Whether the filler is uniformly dispersed inside the particles can be confirmed by observing the surface of the particles using an electron microscope or the like, to ensure uniform dispersion of the filler. Furthermore, although it depends on the physical properties of the filler used, when using a conductive filler, it can be confirmed by measuring the volume resistivity. The volume resistivity is a value measured according to the measurement method (7) described in this specification, and when a conductive filler is used, the volume resistivity is preferably 10⁶ Ω·cm or less. Therefore, to manufacture resin particles in order to uniformly disperse the filler in the hot-melt fluororesin, the method described in Patent Document 2 can be used, for example.
[0031] Various types of fillers can be used as fillers dispersed in particles. Examples include metal powders, metal oxides (alumina, zinc oxide, tin oxide, titanium oxide, etc.), glass, ceramics, silicon carbide (SiC), silicon oxide, boron nitride, calcium fluoride, carbon black, graphite, mica, barium sulfate, and various resin particles. Fillers with various shapes can also be used, such as granular, fibrous, and sheet-like fillers.
[0032] In particular, the present invention is effective when using conductive fillers, and examples of conductive fillers include metals, metal oxides (zinc oxide, tin oxide, titanium oxide, indium oxide, etc.), titanium carbide, titanium nitride, carbon fibers, carbon black, graphite, carbon nanotubes (CNTs), and other carbon materials having a graphene structure, as well as particles and composite particles coated thereon. For high conductivity, a combination of carbon black and carbon fibers is preferably used. Furthermore, in the present invention, materials with relatively low insulation, such as silicon carbide (SiC), and especially materials with a volume resistivity of 10⁸ Ω·cm or less, can also be used as conductive fillers. Silicon carbide (SiC) is preferably used to improve the wear resistance of the coating.
[0033] Furthermore, when using polar particles with hydrophilic surfaces such as mica, alumina, boron nitride, and silicon oxide (the electrical properties of fluoropolymers and fillers differ, therefore charge deviation is expected during electrostatic coating), thick coatings are difficult to achieve, but such fillers can still be used. Mica provides a bright appearance to the coating and is therefore preferred.
[0034] Fillers come in various shapes, such as granular, fibrous, and flake fillers, which can be used as particle shapes. The preferred mixing amount depends on the desired properties and the type and size of the filler, but is preferably from 0.1% to 30% by weight, more preferably from 1% to 10% by weight, and particularly preferably from 2% to 5% by weight. If the filler amount is low, the filler's effectiveness decreases. Furthermore, if the filler amount is high, there is a concern that a smooth and uniform coating may not be obtained due to the filler particles easily agglomerating or having high melt viscosity.
[0035] The average particle size of the first hot-melt fluoropolymer particles is in the range of 2 μm to 100 μm, preferably 3 μm to 75 μm, more preferably 5 μm to 50 μm, and particularly preferably 8 μm to 35 μm. If the average particle size is small, not only is electrostatic powder coating difficult due to the influence of wind, but manufacturing is also difficult in the first place, and aggregation tends to occur during storage, leading to defects. Furthermore, if the average particle size is too large, it is difficult to apply charge, and therefore desorption tends to occur. As a result, electrostatic coating becomes difficult, and the surface of the obtained coating film becomes uneven.
[0036] Note that in this specification, "average particle size" refers to the particle size (d50) at 50% of the integral value of the particle size distribution (based on volume) obtained by laser diffraction / scattering.
[0037] (2) Second hot-melt fluororesin particles
[0038] The second hot-melt fluororesin particle of the present invention is a particle containing hot-melt fluororesin with an average particle size of 10 μm to 200 μm.
[0039] The second hot-melt fluoropolymer particles can be manufactured from the resin used in the first hot-melt fluoropolymer particles. The second hot-melt fluoropolymer particles differ from the first hot-melt fluoropolymer particles in that they do not contain fillers. In hot-melt fluoropolymers, perfluoropolymers, such as PFA and FEP, tetrafluoroethylene, hexafluoropropylene, and perfluoro(alkyl vinyl ether) copolymers, are particularly preferred from the perspective of heat resistance. Among these, PFA is preferred from the perspective of heat resistance.
[0040] The average particle size is in the range of 10 μm to 200 μm, preferably 15 μm to 150 μm, more preferably 20 μm to 100 μm, and particularly preferably 25 μm to 70 μm. When this average particle size is compared with the average particle size of the first hot-melt fluoropolymer particles described above, the average particle size of the second hot-melt fluoropolymer particles is preferably larger than that of the first hot-melt fluoropolymer particles. Commercially available hot-melt fluoropolymer powder coatings can be used. Note that the particles do not contain fillers, but may contain small amounts of additives, such as defoamers, outside the particles (in the powder mixture state).
[0041] (3) Charge control agent particles
[0042] Various types of conductive particles can be used as charge control particles of the present invention. Examples include metal powders, carbon fibers, carbon black, graphite, carbon nanotubes (CNTs) and other carbon materials having a graphene structure, metal oxides (zinc oxide, tin oxide, titanium oxide, indium oxide, etc.), titanium carbide, titanium nitride, etc. Preferably, carbon materials with a graphene structure are used, and particularly preferably, graphite is used. The function of the charge control particles is considered to be that, in the case of differences in electrostatic properties between a first hot-melt fluoropolymer particle containing fillers and a second hot-melt fluoropolymer particle without fillers, the charge control particles adhere to and coat the particles, thereby homogenizing the electrostatic properties of the surface and providing uniform mixing without aggregation and separation when the particles are mixed together. Graphite is preferred herein because dry mixing is carried out at high speed, pulverizing brittle graphite to form flakes that can adhere to and coat the particles.
[0043] (4) Optional components
[0044] The powder coating composition of the present invention may also contain organic / inorganic material additives as optional components, provided that such optional components do not affect the physical properties of the powder coating composition. Examples include polyarylene sulfides, polyetheretherketones, polyamides, polyimides and other engineering plastics, metal powders, metal oxides (alumina, zinc oxide, tin oxide, titanium oxide, etc.), glass, ceramics, silicon carbide, silicon oxide, calcium fluoride, carbon black, graphite, mica, barium sulfate, etc. The additives can be in various shapes, such as particulate, fibrous, or flake fillers. The amount of the additive is preferably 10% by weight or less, and more preferably 5% by weight or less, based on the total amount of the powder coating composition.
[0045] (5) The composition ratio of the powder coating composition of the present invention
[0046] In the powder coating composition of the present invention, the ratio of the first hot-melt fluoropolymer particles to the second hot-melt fluoropolymer particles is preferably in the range of 1 to 60 wt%: 40 to 99 wt%, more preferably 5 to 50 wt%: 50 to 95 wt%, and even more preferably 10 to 45 wt%: 55 to 90 wt%. Furthermore, the amount of charge control agent particles is preferably 0.01 wt% to 5 wt% of the total powder coating composition, more preferably 0.1 wt% to 3.0 wt%, and even more preferably 0.2 wt% to 2.0 wt%. Additionally, the proportion of fluoropolymer in the total powder coating composition is 80 wt% or more, and preferably 90 wt% or more. Increasing the proportion of fluoropolymer allows for the appropriate realization of fluoropolymer properties such as release properties, sliding properties, chemical resistance, and weather resistance. However, decreasing the proportion of fluoropolymer prevents the sufficient realization of these properties.
[0047] (6) Manufacturing method
[0048] The following describes a method for manufacturing the powder coating composition of the present invention.
[0049] The powder coating composition of the present invention is obtained by mixing first hot-melt fluoropolymer particles, second hot-melt fluoropolymer particles, and charge control agent particles. Examples of possible mixing methods include methods of mixing particles under dry conditions (dry blending) and fluid mixing methods using a Turbula mixer, etc., which agitates the mixture by rolling the container itself for mixing. Examples of apparatus for dry blending include, but are not limited to, a cutter mixer, a Henschel mixer, a V-type mixer with a shredder, a double cone mixer with a shredder, a rocking mixer, etc. The mixed resin composition is molded into a prescribed shape according to the intended use.
[0050] (7) Coating film prepared from the powder coating composition of the present invention
[0051] The "coating" of this invention refers to a coating obtained by applying the powder coating composition of this invention. For adhesion to a substrate, a primer layer containing a fluoropolymer is preferably provided and adheres to the substrate. The application method of the powder coating composition of this invention can be any conventionally known powder coating method, but electrostatic powder coating is preferred. After coating, a coating free of pinholes and other defects is obtained by heating to a temperature above the melting point of the hot-melt fluoropolymer. The powder coating composition of this invention is preferably used in: cookware, such as frying pans, rice cookers, etc.; heat-releasing trays in factory production lines (such as bread baking processes); office equipment related products, such as fuser rollers / belts / inkjet nozzles, etc.; industrial equipment related products in chemical plants, such as pipes, etc.; and other products requiring non-stick properties and water and oil resistance.
[0052] Preparation of aluminum test pieces
[0053] (A) Substrate surface treatment (shot peening)
[0054] The surface of the aluminum substrate (JIS A1050 squeezable product, 95mm x 150mm, 1mm thick) was degreased using isopropanol, and then roughened by shot peening using a Numablaster SGF-4(A)S-E566 manufactured by Fuji Manufacturing Co., Ltd. with #60 alumina (Showa Blaster manufactured by ShowaDenko KK).
[0055] (2) Primer application
[0056] Use an air spray gun (W-88-10E2) The nozzle (manual spray gun, manufactured by Anest Iwata Corporation) is applied to the substrate treated in (A) above at 3 kgf / cm². 2 Up to 4 kgf / cm 2 The liquid primer coating (fluoropolymer Teflon (registered trademark) coating, water-based primer PJ-BN910, manufactured by Chemours-Mitsui Fluoroproducts Co., Ltd.) was applied by air pressure spraying. The coating was performed such that the weight of the liquid applied was approximately 0.9 g to 1.4 g per substrate, and then dried in a forced-draft circulating oven at 120°C for 15 minutes to form a coating film with a thickness of 8 μm to 12 μm. The coating environment was a temperature of 25°C and a humidity of 60% RH.
[0057] Evaluation methods
[0058] (1) Coating appearance
[0059] Using an electrostatic powder coating machine (Hand Gun System GX7500CS, manufactured by Nihon Parkerizing Co., Ltd.), the aluminum substrate treated in (A) and (B) above was placed horizontally in a grounded state, and powder was electrostatically coated from a distance of approximately 25 cm at a coating voltage of 20 kV to 40 kV (negative) and a discharge rate of approximately 50 g / min, achieving a coating weight of approximately 2.8 g (corresponding to a film thickness of 100 μm). After baking at 390 °C for 30 minutes, the appearance of the obtained coating was observed. A uniform appearance without any abnormalities was considered acceptable (○).
[0060] (2) Concealment
[0061] Observe the appearance of the coating obtained in (1) above to confirm whether the color of the primer is obscured. The absence of visible base color is considered acceptable (○).
[0062] (3) Thick coating capability 1
[0063] Using an electrostatic powder coating machine (Hand Gun System GX7500CS, manufactured by Nihon Parkerizing Co., Ltd.), the aluminum substrates treated in (A) and (B) above were placed vertically and grounded. Powder was then electrostatically applied from a distance of approximately 25 cm at a coating voltage of 20 kV to 40 kV (negative) and a discharge rate of approximately 50 g / min until the powder no longer adhered. The coating environment was 25°C and 60% RH. The coated aluminum substrate was then baked in a forced-ventilation circulating oven at 390°C for 30 minutes to form a coating film. The coating amount, presence of powder fallout, presence of electrostatic repulsion, and the appearance of the obtained coating film were inspected. A coating with a coating amount of 2.8 g (corresponding to a film thickness of 100 μm) or more, without powder fallout, electrostatic repulsion, blistering, or other defects, was considered acceptable (○).
[0064] (4) Thick coating capability 2
[0065] Electrostatic powder coating was performed on a horizontally mounted glass substrate (float glass, 95mm × 150mm, 2mm thick) using a Hand Gun System GX7500CS powder coater (manufactured by Nihon Parkerizing Co., Ltd.), with film thicknesses ranging from 100μm to 120μm each time. Baking was performed at a specified temperature for 30 minutes, repeated five times (390°C for the first time, 360°C for the second and third times, and 340°C for the fourth and fifth times). The thickness of the baked film was observed to be 500μm or greater, and the presence of defects due to blistering was noted. If the thickness was 500μm and no defects due to blistering were observed, the film was considered acceptable (○).
[0066] (5) Conductivity 1
[0067] Electrostatic coating was performed on a glass substrate (float glass, 95mm × 150mm, 2mm thick) to achieve a film thickness of 100μm to 120μm. After baking at 390°C for 30 minutes, the coating was peeled off in boiling water to obtain the film. The surface resistivity was measured using a UA probe at an applied voltage of 100V using a Hiresta UX (manufactured by Nittoseiko Analytech Co., Ltd.). The surface resistivity was below 10... 9 When Ω is indicated as qualified (○), and when it is 10 10-12 When Ω is indicated as Δ, and above 10 12 When Ω is indicated as ×.
[0068] (6) Conductivity 2
[0069] Coatings with a thickness of 300 μm or more, prepared under the same conditions as in Thick Coating Property 2, were peeled off in boiling water to obtain films. Surface resistivity was measured using a Hiresta UX probe manufactured by Nittoseiko Analytech Co., Ltd., at an applied voltage of 100 V. Surface resistivity below 10... 9 When Ω is indicated as qualified (○), and when it is 10 10 -12 When Ω is indicated as Δ, and above 10 12 When Ω is indicated as ×.
[0070] (7) Volume resistivity
[0071] Electrostatic coating was performed on a glass substrate (float glass, 95mm × 150mm, 2mm thick) to achieve a film thickness of 50μm to 100μm. After baking at 390°C for 30 minutes, the coating was peeled off in boiling water to obtain the film. The film was peeled off, and the resistivity along the thickness direction (front and back surfaces) of the coating was measured using a UA probe on a Hiresta UX (manufactured by Nittoseiko Analytech Co., Ltd.) at an applied voltage of 100V, thereby calculating the volume resistivity. If the volume resistivity is less than 10... 6 If the value is Ω·cm, then the particle used is considered advantageous.
[0072] raw material
[0073] • Carbon Black 1: "Asahi Thermal" manufactured by Asahi Carbon Co., Ltd., with an average primary particle size of 80nm (oil furnace carbon black).
[0074] • Carbon Black 2: Carbon ECP (KETJENBLACK) manufactured by Lion Specialty Chemicals Co., Ltd., with an average primary particle size of 25 nm.
[0075] • Carbon fiber (Torayca Milled Fiber MLD-30 manufactured by Toray Industries, Inc., average length: 30 μm)
[0076] • Graphite (UF-G5 manufactured by ShowaDenko KK, average particle size: 3μm)
[0077] PFA aqueous dispersion
[0078] Aqueous dispersions of PFA were prepared as follows. Dispersions of tetrafluoroethylene / perfluoropropyl vinyl ether (TFE / PPVE) copolymers were prepared according to the methods described in Examples 1 to 3 of Japanese Patent Publication 5588679. (MFR of solid resin: 16.6 [g / 10 min], average particle size: 0.186 μm, comonomer (PPVE) ratio: 3.3 wt%, PFA content in dispersion: 30.6 wt%)
[0079] • PFA powder coating: Teflon (registered trademark) fluoropolymer powder topcoat MJ-508 manufactured by Chemours-Mitsui Fluoroproducts Co., Ltd., with an average particle size d50 of approximately 50 μm (a mixture of powdered amorphous particles and 3% PPS particles (to suppress foaming)).
[0080] ·2H,3H-Decafluoropentane (Vertrel (registered trademark) XF manufactured by Chemours-Mitsui Fluoroproducts Co., Ltd.)
[0081] • 60% Nitric Acid (manufactured by FUJIFILM Wako Pure Chemical Corporation)
[0082] • Silicon carbide (SiC) (spherical powder particles with an average particle size of approximately 25 μm)
[0083] • Mica (IRIODIN 355 manufactured by MERCK KGAA, a flaky powder with a particle size of 10 μm to 100 μm)
[0084] Example
[0085] Comparative Example 1
[0086] Preparation Example of First Hot-Melt Fluoropolymer Particle 1
[0087] 1000g of pure water was collected in a 2L stainless steel beaker, and 29.5g of carbon black 2 (KETJENBLACK) and 9.0g of graphite were added. The mixture was then ultrasonically dispersed for 5 minutes using an ultrasonic generator (UE-100Z28S-8A ultrasonic generator, manufactured by Ultrasonic Engineering Co., Ltd.). The resulting dispersion was further added to a stainless steel container containing 4200g of PFA aqueous dispersion and stirred at 600rpm for 3 minutes using a downflow propeller-type 4-blade stirrer. Then, 88g of 60% nitric acid aqueous solution was added, and after confirming a sharp increase in viscosity, 1000g of 2H,3H-decafluoropentane was added to generate coarse aggregate particles in the liquid. The coarse aggregate particles removed by filtration were washed with pure water, and the 2H,3H-decafluoropentane was volatilized and removed by raising the temperature to 50°C to 60°C and then maintaining it for 30 minutes. The obtained dry coarse particles were pulverized using a pulverizer (RP-6-K115 manufactured by Rietz Manufacturing) to obtain pulverized powder. The pulverized powder of the aggregates was sprayed and baked in a baking oven described in Patent Document 3. The particles cooled below their melting point were collected and then used as first hot-melt fluoropolymer particles 1. The average particle size of the obtained particles was d50: 31.4 μm. The volume resistivity of particle 1 was measured according to evaluation method (7), and the result was 10. 5 -10 6 Ω·cm. The various evaluations described above were conducted using this particle (powder) as a powder coating composition.
[0088] Comparative Example 2
[0089] 40.0 g of the first hot-melt fluoropolymer particles 1 (average particle size d50: 31.4 μm) prepared in the above preparation example and 60.0 g of PFA powder coating (MJ-508, manufactured by Chemours-Mitsui Fluoroproducts Co., Ltd., average particle size d50: 55.0 μm) as the second hot-melt fluoropolymer were placed in a high-speed mixer (KSMAX, manufactured by TANINAKA) and then mixed and stirred at 12,000 rpm for 30 seconds to obtain a powder coating composition.
[0090] Example 1
[0091] 20.0 g of the first hot-melt fluoropolymer particles (average particle size d50: 31.4 μm) prepared in Example 1 above, 79.4 g of PFA powder coating (MJ-508, manufactured by Chemours-Mitsui Fluoroproducts Co., Ltd., average particle size d50: 51.2 μm) as the second hot-melt fluoropolymer, and 0.6 g of graphite were placed in a high-speed mixer (KSMAX, manufactured by TANINAKA) and then mixed and stirred at 12,000 rpm for 30 seconds to obtain a powder coating composition.
[0092] Example 2
[0093] The powder coating composition was obtained by a method similar to that of Example 1 above, except that 79.1g of PFA powder coating (second hot-melt fluoropolymer) was used instead of 79.4g, and 0.9g of graphite was used instead of 0.6g.
[0094] Preparation Example of First Hot-Melt Fluoropolymer Particle 2
[0095] The first hot-melt fluoropolymer particles 2 were manufactured using a method similar to that used in Comparative Example 1 (Preparation Example of First Hot-Melt Fluoropolymer Particle 1), except that carbon black 1 was used instead of carbon black 2 (KETJENBLACK) and graphite. The average particle size of the obtained particles was d50: 22.2 μm. The volume resistivity of particles 2 was measured according to evaluation method (7), and the result was 10. 12 Ω·cm or above.
[0096] Example 3
[0097] The powder coating composition was obtained by a method similar to that of Example 2 above, except that 20.0 g of the first hot-melt fluoropolymer particles 2 (average particle size d50: 22.2 μm) manufactured in the preparation example above was used instead of the first hot-melt fluoropolymer particles manufactured in Preparation Example 1 above, and PFA powder coating (MJ-508, manufactured by Chemours-Mitsui Fluoroproducts Co., Ltd., average particle size d50: 42.8 μm) was used as the second hot-melt fluoropolymer.
[0098] Example 4
[0099] The powder coating composition was obtained by a method similar to that in Example 3 above, except that 79.5g of PFA powder coating was used instead of 79.1g, and 0.5g of graphite was used instead of 0.9g.
[0100] Example 5
[0101] The powder coating composition was obtained by a method similar to that in Example 3 above, except that 79.7g of PFA powder coating was used instead of 79.1g, and 0.3g of graphite was used instead of 0.9g.
[0102] Results of Comparative Examples 1 and 2 and Examples 1 to 5
[0103] Tables 1 and 2 show the composition ratios and coating film evaluation results of the powder coating compositions of Comparative Examples 1 and 2, and Examples 1 to 5. Table 1 summarizes the composition ratios of the powder coating compositions of the present invention. Table 2 shows the evaluation results measured according to evaluation methods (1) to (6). Comparative Example 1 provides a coating film formed from first hot-melt fluoropolymer particles 1. However, (1) coating appearance (uniform and no appearance abnormalities: ○), (2) concealment (whether the base color is not visible: ○), and (3) thickness coating 1 (whether a coating film of 100 μm or more can be formed by coating once on a vertical surface: ○) are not satisfactory.
[0104] ○) are all sufficient, but (4) Thickness coating 2 (whether a coating of 500 μm or thicker can be formed by repeated coating: ○) was not satisfied.
[0105] On the other hand, Comparative Example 2 provides a coating film obtained from the first hot-melt fluoropolymer particles 1 and the second hot-melt fluoropolymer particles. However, although the coating thickness 2 (forming a coating film of 500 μm or more by repeated coating) is sufficient, items (1) to (3) are not satisfied.
[0106] In contrast, Examples 1 and 2 (where graphite was included as a charge control particle and used as the third component in the powder coating composition of Comparative Example 2) achieved good results in all items (1) to (4). In Examples 3 to 5, the conductive particles to be dispersed in the first hot-melt fluoropolymer particles 2 were changed to carbon black 1 only, but the same good results were obtained as in Examples 1 and 2, which included graphite and carbon black 2 (KETJENBLACK).
[0107] Table 1
[0108] Composition of the powder coating compositions of Comparative Examples 1 and 2 and Examples 1 to 5
[0109]
[0110] Table 2
[0111] Evaluation results of Comparative Examples 1 and 2 and Examples 1 to 5
[0112]
[0113]
[0114] Preparation Example of First Hot-Melt Fluoropolymer Particle 3
[0115] 1000g of pure water was collected in a 2L stainless steel beaker, and 18g of carbon black 2 (KETJENBLACK) and 26g of carbon fiber were added. The mixture was then ultrasonically dispersed for 5 minutes using an ultrasonic generator (UE-100Z28S-8A ultrasonic generator, manufactured by Ultrasonic Engineering Co., Ltd.). The resulting dispersion solution was added to a stainless steel container containing 4200g of PFA aqueous dispersion and stirred at 600rpm for 3 minutes using a downflow propeller-type 4-blade stirrer. Then, 88g of 60% nitric acid aqueous solution was added, and after confirming a sharp increase in viscosity, 1000g of 2H,3H-decafluoropentane was added to generate coarse aggregate particles in the liquid. The coarse aggregate particles removed by filtration were washed with pure water, and the 2H,3H-decafluoropentane was volatilized and removed by raising the temperature to 50°C to 60°C and then maintaining it for 30 minutes. The obtained dry coarse particles were pulverized using a pulverizer (RP-6-K115 manufactured by Rietz Manufacturing) to obtain pulverized powder. The pulverized powder of the aggregates was sprayed and baked in a baking oven described in Patent Document 3. The particles cooled below their melting point were collected and then used as first hot-melt fluoropolymer particles 3. The average particle size of the obtained particles was d50: 17.6 μm. The volume resistivity of particles 3 was measured according to evaluation method (7), and the result was 10. 5 -10 6 Ω·cm.
[0116] Example 6
[0117] 10.0 g of the first hot-melt fluoropolymer particles 3 (average particle size d50: 17.6 μm) prepared in the above preparation example, 89.1 g of PFA powder coating (MJ-508, manufactured by Chemours-Mitsui Fluoroproducts Co., Ltd., average particle size d50: 49.2 μm) as the second hot-melt fluoropolymer particles, and 0.9 g of graphite were placed in a high-speed mixer (KSMAX, manufactured by TANINAKA) and then mixed and stirred at 12,000 rpm for 30 seconds to obtain a powder coating composition.
[0118] Example 7
[0119] The powder coating composition was obtained by a method similar to that of Example 6, except that 20.0 g of the first hot-melt fluoropolymer particles 3 was used instead of 10.0 g, and 79.1 g of PFA powder coating (second hot-melt fluoropolymer) was used instead of 89.1 g.
[0120] Example 8
[0121] The powder coating composition was obtained by a method similar to that of Example 6, except that 40.0 g of the first hot-melt fluoropolymer particles 3 was used instead of 10.0 g, and 59.1 g of PFA powder coating (second hot-melt fluoropolymer) was used instead of 89.1 g.
[0122] Preparation Example of First Hot-Melt Fluoropolymer Particle 4
[0123] The first hot-melt fluoropolymer particles 4 were manufactured using a method similar to that used in the preparation example of the first hot-melt fluoropolymer particles 3, except that the amounts of carbon black 2 and PFA aqueous dispersion were changed. The average particle size of the obtained particles was d50: 18.4 μm. The volume resistivity of particles 4 was measured according to evaluation method (7), and the result was 10. 5 -10 6 Ω·cm.
[0124] Example 9
[0125] The powder coating composition was obtained by a method similar to that of Example 6, except that the first hot-melt fluoropolymer particles 4 (average particle size d50: 18.4 μg) were used instead of the first hot-melt fluoropolymer particles 3.
[0126] Example 10
[0127] The powder coating composition was obtained by a method similar to that of Example 7, except that the first hot-melt fluoropolymer particles 4 (average particle size d50: 18.4 μg) were used instead of the first hot-melt fluoropolymer particles 3.
[0128] Example 11
[0129] The powder coating composition was obtained by a method similar to that of Example 8, except that the first hot-melt fluoropolymer particles 4 (average particle size d50: 18.4 μg) were used instead of the first hot-melt fluoropolymer particles 3.
[0130] Results of Examples 6 to 11
[0131] Tables 3 and 4 show the composition ratios and coating evaluation results of the powder coating compositions of Examples 6 to 11. Table 3 summarizes the composition ratios of the powder coating compositions of the present invention. Table 4 shows the evaluation results measured according to evaluation methods (1) to (6). Examples 6 to 11 used carbon black 2 (KETJENBLACK) and particles in which carbon fibers are dispersed as first hot-melt fluoropolymer particles 3. In Example 6, (1) for coating thickness 1, it was confirmed that more than 2.8 g of coating could be applied without powder falling onto vertical surfaces and without causing electrostatic repulsion, and it was confirmed that there were no abnormalities in the appearance of the coating film. (2) for coating thickness 2, after electrodeposition of powder and repeated coating and baking, a film with a thickness of 500 μm or more was obtained that did not bubble even after baking. (3) for conductivity 1, a film with a thickness of about 100 μm exhibited a surface resistance value of 106-107 Ω. (4) Regarding conductivity 2, a surface resistivity of 10⁶-10⁷ Ω is exhibited in films with a thickness of 300 μm or more. (5) Regarding coating appearance, a smooth and uniform coating is obtained. (6) Regarding concealment, a coating with a sufficiently concealing primer is obtained. For Examples 7 to 11, good results were obtained in almost all aspects, similar to Example 6.
[0132] In Examples 6 to 11, compared to Examples 1 to 5, by using carbon black 2 (KETJENBLACK) and particles in which carbon fibers are dispersed as the first hot-melt fluororesin particles, approximately 10 were observed for both (5) conductivity 1 (resistance value of the 100 μm coating) and (6) conductivity 2 (resistance value of the 300 μm coating). 6 Ω has good electrical conductivity.
[0133] Table 3
[0134] Composition of the powder coating compositions in Examples 6 to 11
[0135]
[0136] Table 4
[0137]
[0138]
[0139] Preparation Example of First Hot-Melt Fluoropolymer Particle 5
[0140] The first hot-melt fluoropolymer particles 5 were manufactured using a method similar to that used in the preparation of the first hot-melt fluoropolymer particles 3, except that the amounts of carbon black 2 and PFA aqueous dispersion were changed. The average particle size of the obtained particles was d50: 20.2 μm. The volume resistivity of particles 5 was measured according to evaluation method (7), and the result was 10. 5 -10 6 Ω·cm.
[0141] Example 12
[0142] The powder coating composition was obtained by a method similar to that of Example 6, except that the first hot-melt fluoropolymer particles 5 (average particle size d50: 20.2 μg) were used instead of the first hot-melt fluoropolymer particles 3.
[0143] Example 13
[0144] The powder coating composition was obtained by a method similar to that of Example 7, except that the first hot-melt fluoropolymer particles 5 (average particle size d50: 20.2 μg) were used instead of the first hot-melt fluoropolymer particles 3.
[0145] Example 14
[0146] The powder coating composition was obtained by a method similar to that of Example 12, except that 30.0 g of the first hot-melt fluoropolymer particles 5 (average particle size d50: 20.2 μm) was used instead of 10.0 g, and 69.1 g of PFA powder coating (second hot-melt fluoropolymer) was used instead of 89.1 g.
[0147] Example 15
[0148] The powder coating composition was obtained by a method similar to that of Example 8, except that the first hot-melt fluoropolymer particles 5 (average particle size d50: 20.2 μg) were used instead of the first hot-melt fluoropolymer particles 3.
[0149] Example 16
[0150] The powder coating composition was obtained by a method similar to that of Example 13, except that 78.65g of PFA powder coating (second hot-melt fluoropolymer) was used instead of 79.1g, and 1.35g of graphite was used instead of 0.9g.
[0151] Results of Examples 12 to 16
[0152] Tables 5 and 6 show the composition ratios and coating evaluation results of the powder coating compositions of Examples 12 to 16. Table 5 summarizes the composition ratios of the powder coating compositions of the present invention. Table 6 shows the evaluation results measured according to evaluation methods (1) to (6). For all Examples 12 to 16, good results were obtained in all of the following items: (1) coating appearance, (2) concealment, (3) thick coating capability 1, (4) thick coating capability 2, (5) conductivity 1, and (6) conductivity 2. However, regarding (6) conductivity 2, the surface resistance showed an increasing trend as the ratio of the first particle to the second particle increased (the increasing trend in Examples 12 to 15).
[0153] Table 5
[0154] Composition of the powder coating compositions in Examples 12 to 16
[0155]
[0156] Table 6
[0157] Evaluation results of Examples 12 to 16
[0158]
[0159] Preparation Example of First Hot-Melt Fluoropolymer Particle 6
[0160] The first hot-melt fluoropolymer particles 6 (containing 5% by weight SiC) were manufactured using a method similar to that used in the preparation example of the first hot-melt fluoropolymer particles 2, except that SiC was used instead of carbon black 1, and the amount of SiC and the amount of PFA aqueous dispersion were varied. The average particle size of the obtained particles was d50: 21.0 μm.
[0161] Example 17
[0162] The powder coating composition (PFA powder coating: 79.7 wt%, graphite: 0.3 wt%, particles 6: 20.0 wt%) was obtained by a method similar to that of Example 5, except that the first hot-melt fluoropolymer particles 6 (average particle size d50: 21.0 μm) were used instead of the first hot-melt fluoropolymer particles 2.
[0163] Comparative Example 3
[0164] The powder coating composition (PFA powder coating: 80% by weight, particles 6: 20% by weight) was obtained using a method similar to that described in Example 17 above, except that graphite was removed from the powder coating composition.
[0165] Comparative Example 4
[0166] Powder coating compositions are prepared solely from the first hot-melt fluoropolymer particles 6.
[0167] Preparation Example of First Hot-Melt Fluoropolymer Particles 7
[0168] The first hot-melt fluoropolymer particles 7 (containing 1% by weight of mica) were manufactured using a method similar to that used in the preparation example of the first hot-melt fluoropolymer particles 6, except that mica was used instead of SiC, and the amounts of mica and the PFA aqueous dispersion were varied. The average particle size of the obtained particles was d50: 21.1 μm.
[0169] Example 18
[0170] The powder coating composition (PFA powder coating: 79.7 wt%, graphite: 0.3 wt%, particles 7: 20 wt%) was obtained by a method similar to that of Example 5, except that the first hot-melt fluoropolymer particles 7 (average particle size d50: 21.1 μm) were used instead of the first hot-melt fluoropolymer particles 2.
[0171] Comparative Example 5
[0172] The powder coating composition (PFA powder coating: 80% by weight, particles 7: 20% by weight) was obtained using a method similar to that described in Example 18 above, except that graphite was removed from the powder coating composition.
[0173] Comparative Example 6
[0174] Powder coating compositions are prepared solely from the first hot-melt fluoropolymer particles 7.
[0175] Results of Examples 17 and 18 and Comparative Examples 3 to 6
[0176] Tables 7 and 8 show the composition ratios and coating evaluation results of the powder coating compositions of Examples 17 and 18 and Comparative Examples 3 to 6. Table 7 summarizes the composition ratios of the powder coating compositions of the present invention. Table 8 shows the evaluation results measured according to evaluation methods (1) to (3). The results of Examples 17 and 18 confirm that adding graphite as a third component improves (1) coating appearance, (2) concealment and (3) thick coating properties 1, in the same way as when using resin particles containing carbon black, etc., even when using first hot-melt fluoropolymer particles containing non-conductive fillers (such as SiC, mica, etc.). On the other hand, when graphite is not included as a third component (Comparative Examples 3 and 5), (1) coating appearance is uneven and (2) concealment is insufficient. Furthermore, when the powder coating composition is made only from hot-melt fluoropolymer particles 6 and 7 (Comparative Examples 4 and 6), (1) coating appearance and (2) concealment are satisfactory, but (3) thick coating properties 1 are problematic.
[0177] Table 7
[0178] Composition of the powder coating compositions of Examples 17 and 18 and Comparative Examples 3 to 6
[0179]
[0180]
[0181] Table 8
[0182] Evaluation results of Examples 17 and 18 and Comparative Examples 3 to 6
[0183]
[0184] This invention is not limited to the embodiments described in this specification or the implementations of the invention disclosed in this specification, but also covers the invention with appropriate modifications based on the details disclosed in this specification, as long as such modifications do not substantially conflict with the invention.
[0185] Industrial applicability
[0186] The hot-melt fluoropolymer powder coating composition of the present invention can be applied to a vertical surface by electrostatic powder coating, forming a fairly thick coating film on a wide range of industrial products, and the coating film can be endowed with properties (such as conductivity) by the fillers contained therein.
Claims
1. A powder coating composition, said powder coating composition being a powder mixture comprising: First hot-melt fluoropolymer particles, having an average particle size of 2µm to 100µm, wherein filler is dispersed in the particles; Second hot-melt fluoropolymer particles having an average particle size of 10µm to 200µm, wherein the average particle size of the second hot-melt fluoropolymer particles is larger than the average particle size of the first hot-melt fluoropolymer particles, and wherein the second hot-melt fluoropolymer particles do not contain the filler; and Charge control agent particles.
2. The powder coating composition according to claim 1, wherein the ratio of the first hot-melt fluoropolymer particles to the second hot-melt fluoropolymer particles is 1 to 60% by weight: 40 to 99% by weight, and the amount of the charge control agent particles is 0.01% to 5% by weight of the total amount of the powder coating composition.
3. The powder coating composition according to any one of claims 1 to 2, wherein the filler is a conductive filler.
4. The powder coating composition according to claim 3, wherein the conductive filler is a carbon material having a graphene structure.
5. The powder coating composition according to any one of claims 1 to 4, wherein the charge control agent particles are graphite.
6. The powder coating composition according to any one of claims 1 to 5, wherein the hot-melt fluoropolymer is a perfluorinated resin.
7. A coating film made from the powder coating composition according to any one of claims 1 to 6, wherein the film thickness is 100 µm or more.
Citation Information
Patent Citations
Preparation of ground fish meat
JP1980088679A
Display control unit and method for controlling the same
JP2021026033A
Sprayable powder of non-fibrillatable fluoropolymer
US6518349B1